Cell Membrane-Camouflaged Nanoparticles: A Promising Biomimetic Platform for Tumor Therapy - Chengliang Lyu; Wenjin Wang; Yuan Yang; Peilin Guo; Feng Li; Wei Wei (Journal of Chemical Engineering of Japan)
Over the past several decades, nanoparticles (NPs) have attracted considerable attention for anti-tumor treatment. However, exogenous NPs directly exposed to the physiological environment are easily recognized as foreign substances and rapidly eliminated by the immune system. Cell membrane camouflaging can provide “stealth” ability to NPs for avoiding recognition and elimination by the immune system, and endows NPs with diverse functionalities via inheriting the functions of parent cells, representing a facile top-down approach for multi-functionalization. In this review, we discuss the unique biomedical tasks performed by cell membrane-camouflaged NPs for tumor therapy in term of circulation, targeting, and immunity. In addition to the intrinsic functions derived from the cell membrane camouflaging, we introduce further improvements in cell membrane-camouflaged NPs via additional functionalities and combinations with novel technologies. Finally, we highlight the current challenges and prospects of these cell membrane camouflaging therapeutics that will contribute to the development.